Methanol steam reforming for hydrogen generation via conventional and membrane reactors: A review - P. Ribeirinha (2014)
In the recent years, hydrogen has gained a considerable interest as an energy carrier useful for various applications and, particularly, for polymer electrolyte membrane fuel cells (PEMFCs) supply. Nevertheless, PEMFCs require high purity hydrogen as a feeding fuel, which shows some limitations regarding storage and transportation. Therefore, to overcome these problems, the in situ hydrogen generation has made attractive both alcohols and hydrocarbons steam reforming reaction. Among other fuels, methanol is an interesting hydrogen source because it is liquid at ambient conditions, possesses relatively high H/C ratio, low reforming temperature (200-300 1C) and it is also producible from biomass. Meanwhile, there is a comprehensive literature about inorganic membrane reactors utilization for hydrogen generation via methanol steam reforming reaction. This review illustrates the earlier state of the art from an experimental point of view about hydrogen production from methanol reforming performed in both conventional and membrane reactors. Furthermore, a short overview about methanol reforming catalysts as well as a discussion on the impact of methanol steam reforming process via inorganic membrane reactors to produce hydrogen for PEMFCs supply is given.